Kulturanasan Promoting Historical Heritage and Culture Appreciation through the integration of the Estacion de Barasoain Y Malolos with the Malolos NSCR station. - Dayrit, Vincent P.; Nadal, Cathe Desiree S.; Fontanoza, Franklin Jr. S. (Quezon City College of Architecture, University of the Philippines Diliman, 2024)
Kulturanasan generates a landscape proposal along the Malolos NSCR Station within
Bulacan to help revive the historical heritage of Malolos and promote cultural
appreciation. The thesis attempts to effectively adapt to the negative effects of
urbanization that may be caused by the opening of the NSCR transport hub through an
experiential network and plaza center celebrating the history and culture of city. The
project aims to integrate mixed-use development within the delineation of the site,
providing an immersive experience to users while improving upon pedestrian access,
connectivity, wayfinding, and mass transportation.
The thesis adapts a design proposal that utilizes the Cultural Intelligence Model and
the 5Ds model, leveraging the Estacion de Barasoin as a cultural catalyst serving as a
central network relative to the heritage properties of Malolos. Through stakeholder
survey and key informant interview, the design integrated the city’s cultural properties
of Malolos to the transit-oriented development, offering a balance between efficient
and fast-moving spaces, and cultural landscapes.
The thesis developed a cultural plaza development as a central hub to help the city of
Malolos in properly maintaining its cultural navigation, promoting cultural
appreciation and preserving its historical heritage. As a key component in urban
planning, the introduction of experiential landscapes to transport hubs promoted
mass transit and effective urban mobility while integrating culture into mixed
transport systems.
Include appendices
Thesis (Bachelor of Landscape Architecture) -- University of the Philippines Diliman
Keywords: Urbanization -- Malolos (Bulacan); Terminals (Transportation) -- Malolos (Bulacan); Mixed-use development -- Malolos (Bulacan); Historic sites -- Malolos (Bulacan); Culture